2012
DOI: 10.1007/s00425-012-1605-2
|View full text |Cite
|
Sign up to set email alerts
|

Chlapsin, a chloroplastidial aspartic proteinase from the green algae Chlamydomonas reinhardtii

Abstract: Aspartic proteinases have been extensively characterized in land plants but up to now no evidences for their presence in green algae group have yet been reported in literature. Here we report on the identification of the first (and only) typical aspartic proteinase from Chlamydomonas reinhardtii. This enzyme, named chlapsin, was shown to maintain the primary structure organization of typical plant aspartic proteinases but comprising distinct features, such as similar catalytic motifs DTG/DTG resembling those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
7
0
4
Order By: Relevance
“…In a more recently published report, Paparelli et al [94] have identified a chloroplast-located AP gene NANA whose misexpression or overexpression not only influences photosynthetic carbohydrate metabolism but also plastid and nuclear gene expression [94]. So the localization of these AP genes to the Arabidopsis or grape thylakoid membranes raises the possibility that they may fulfill roles as specific processing enzymes in this organelle, or participate in maintenance or degradation of photosystem proteins [7,95]. …”
Section: Discussionmentioning
confidence: 99%
“…In a more recently published report, Paparelli et al [94] have identified a chloroplast-located AP gene NANA whose misexpression or overexpression not only influences photosynthetic carbohydrate metabolism but also plastid and nuclear gene expression [94]. So the localization of these AP genes to the Arabidopsis or grape thylakoid membranes raises the possibility that they may fulfill roles as specific processing enzymes in this organelle, or participate in maintenance or degradation of photosystem proteins [7,95]. …”
Section: Discussionmentioning
confidence: 99%
“…Aspartic protease (AP, EC 3.4.23), a versatile proteolytic enzyme, can be applied in various industrial processes (Jamdar & Harikumar, 2016 ;Yegin et al, 2011 ). Diverse aspartic proteases from different sources have been reported and characterized (Almeida et al, 2012 ;da Silvaa et al, 2017 ). However, the identification and detailed properties of aspartic proteases from psychrophilic fungi have not been reported till date.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a su localización subcelular, las PAs de plantas de la familia A1 que han sido caracterizadas, se dirigen principalmente a las vacuolas líticas o al compartimento vacuolar de almacenamiento. Sin embargo, algunas de ellas, se dirigen al retículo endoplasmático o se secretan a la pared celular o al apoplasto (Almeida et al, 2012;González-Rábade et al, 2011;Mazorra-Manzano et al, 2013;van der Hoorn, 2008). Algunos ejemplos de PAs secretadas a la matriz extracelular lo constituyen las PAs de hojas de tabaco 1.…”
Section: Peptidasas De Plantasunclassified
“…Los dos motivos de secuencia catalíticos DTG/DSG se encuentran en todas las PAs de plantas pertenecientes a la familia A1 con la excepción de chlapsina, la PA de Chlamydomonas reinhardtii que contiene DTG/DTG al igual que las peptidasas homólogas animales y microbianas (Almeida et al, 2012). En algunas PAs de hongos y de protozoos, los residuos de ácido aspártico catalíticos también se encuentran dentro de los motivos DTG/DSG.…”
Section: Discusión Y Conclusionesunclassified